PENDAMPINGAN UJIAN NASIONAL UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR EKONOMI - Fahrurrozi, Muhammad; Muhammad, Farhana; Prio Utomo, Danang; Nahdi, Khirjan; Lutfi, Samsul; Zamroni Uska, Muhammad; Usuluddin, Usuluddin; Susilawati, Susilawati (Jurnal Abdimas Musi Charitas, 2020)
Among other things, the teacher's tasks include planning and implementing the process of teaching and learning activities and evaluating student learning outcomes. The role of the teacher in learning is the educator, the model, and the instructor and tutor. Learning success is measured based on the achievement of competencies established since the beginning of the learning activities. Learning assistance at MA NW Lepak, which has been carried out by the PPM Hamzanwadi University team can increase student motivation, it is seen from 65% of students in the category of high and very high learning motivation. Learning outcomes increase after mentoring, viewed from learning outcomes with an increasing trend. The distribution of student learning outcomes in the excellent category from 17% increased to 26%, and the good category from 30% to 32%. Whereas for students whose categories failed to drop from 9% to 0%.